Woman and Home: the Domestic Setting of Late Medieval Spirituality - Webb, Diana M. (Studies in church history, 1990)
‘From the earliest days of Christianity, the domestic community has served as a unit of worship’. In the later medieval period, the home certainly played an important part in the religious observances of many laypeople. By the fifteenth century in England, chapels in private houses were increasingly common, even if they were simply small rooms adapted for the purpose. The practice of informal prayer and private devotional reading did not require special accommodation. We know that individuals prayed in their bedrooms, while Italian women were encouraged to have a bedroom image of the Virgin and to conduct themselves properly in her presence. Italian preachers also thought that children should join in holy play-acting at home, and that they should set up and decorate toy altars. The garden, too, could furnish a setting for the spiritual life. Agnes Paston gives us a haunting glimpse of the life and death of a pious layman in 1453: